2022
DOI: 10.1002/mrd.23639
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of melatonin receptor type 1 in the sheep ovary and involvement of the PI3K/Akt/FOXO3a signaling pathway in the effects of melatonin on survival and in vitro activation of primordial follicles

Abstract: This study characterized the expression of melatonin receptor type 1 (MT 1 ) protein in sheep ovaries, evaluated melatonin effects on primordial follicle survival and development after in vitro culture of ovarian tissue and verified the possible involvement of the phosphatidylinositol-3-kinase/protein kinase B/forkhead box O3a (PI3K/Akt/FOXO3a) pathway in the melatonin actions. Ovine ovarian fragments were cultured in α-modified minimum essential medium alone (α-MEM + ) or supplemented with 100, 500, or 1000 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…In our study, we observed a down-regulation of FOXO3A in POI-GCs. FOXO3A is known to encode a master regulator and potent suppressor of ovarian development [2,43], and its loss of function in mice leads to POI as a result of global follicle activation [44]. Consistent with these findings, we found that MT treatment effectively activated FOXO3A, and silencing FOXO3A significantly attenuated the function of MT.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, we observed a down-regulation of FOXO3A in POI-GCs. FOXO3A is known to encode a master regulator and potent suppressor of ovarian development [2,43], and its loss of function in mice leads to POI as a result of global follicle activation [44]. Consistent with these findings, we found that MT treatment effectively activated FOXO3A, and silencing FOXO3A significantly attenuated the function of MT.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, the classic membrane receptors for melatonin, MT1 and MT2, are found in several areas of the ovary, e.g., oocyte, granulosa cells, luteal cells, etc. [ 48 , 49 , 50 , 51 ].…”
Section: Melatonin: Redox Mechanisms For Preserving Reproductive Healthmentioning
confidence: 99%